DEVELOPMENT AND EVALUATION OF MODELS FOR THE RELATIONSHIP BETWEEN HEIGHT AND DIAMETER OF THREE FOREST STATES FOR TROPICAL RAINFORESTS IN VIETNAM - Thi Thu Hien, Cao; The Anh, Pham; Tuan Anh, Le; Tien Hung, Vu; Viet Duc, Vi (Journal of Forestry Science and Technology, 2020)
This paper introduces the result of finding the best equation to describe the relationship between the total tree height and diameter at breast height of three forest states, including: poor, medium and rich forest states. Data were collected on 15 sample plots, each plot area was 10,000 m2 (100 m x 100 m) in Ha Tinh, Tuyen Quang, Hoa Binh, Quang Binh, Thua Thien Hue and Gia Lai Provinces. 10 different types of equations were tested in this study, including two types of equations, linear equations and nonlinear equations. Based on four criteria to choose the best equation, namely (1) Root of mean square error (RMSE), (2) Adjusted coefficient of determination (R2adj), (3) Bias and (4) Akaike’s information criterion (AIC). The results showed that, equation (3) (h = a0 + a1.d + a2.d2) was the most appropriate to describe the relationship between height and diameter for two forest states, namely poor forest and medium forest, while equation (8) (h = a0.e-a1/d^a2) were recommended for predicting tree height of the rich forest state. Clearly, diameter at breast height was the primary stand variable that influenced the height-dbh relationship. The method and the recommended equations developed in this study were statistically reliable for applications in height estimation for tropical rainforest in Vietnam